2009
DOI: 10.1177/0003065109333357
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Defensive Functioning in Completed Psychoanalyses: the Penn Psychoanalytic Treatment Collection

Abstract: Theory predicts that patients completing psychoanalysis should improve in their dynamic functioning. The aim of this naturalistic study is to examine whether a sample of 17 subjects from the Penn Psychoanalytic Treatment Collection with completed, tape-recorded psychoanalyses demonstrated improvement in one dynamic aspect: their defense mechanisms. The pre-post effect size for the change in overall defensive functioning (ODF) of the sample was large (.76) and statistically significant ( p = .01). The percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Research has shown that a key indicator of successful psychodynamic psychotherapy is when patients use more adaptive defenses and less maladaptive defenses by the end of treatment [e.g., [7][8][9][10][11][12]. Research also indicates that improvement in patient defensive functioning is related to improved patient mental health years after treatment, reduced dropout rates, and successful outcomes [e.g., 10].…”
Section: Interpretations Patient Defensive Functioning and Therapeumentioning
confidence: 99%
“…Research has shown that a key indicator of successful psychodynamic psychotherapy is when patients use more adaptive defenses and less maladaptive defenses by the end of treatment [e.g., [7][8][9][10][11][12]. Research also indicates that improvement in patient defensive functioning is related to improved patient mental health years after treatment, reduced dropout rates, and successful outcomes [e.g., 10].…”
Section: Interpretations Patient Defensive Functioning and Therapeumentioning
confidence: 99%
“…This research has led to several reviews that synthesize the theoretical, methodological, and empirical aspects of defenses [16][17][18]. There is evidence showing that patients who undergo successful psychodynamic treatment demonstrate more adaptive defense use [19][20][21][22][23][24][25][26][27]. Furthermore, the use of mature defenses has been shown to be associated with healthy psychological and physical functioning [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Wogan & Norcross [21] study did not examine defenses or the interpretation of defenses when surveying dynamic therapists. This is surprising as there is a growing body of research demonstrating the importance of adaptive patient defense use and its relationship to positive therapy process and outcome [9,22]. Additionally, there is a body of research that demonstrates positive relationship between the interpretation of defenses and outcome [23].…”
mentioning
confidence: 99%